2018
DOI: 10.1016/j.jpsychires.2018.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Altered neural encoding of prediction errors in assault-related posttraumatic stress disorder

Abstract: Posttraumatic stress disorder (PTSD) is widely associated with deficits in extinguishing learned fear responses, which relies on mechanisms of reinforcement learning (e.g., updating expectations based on prediction errors). However, the degree to which PTSD is associated with impairments in general reinforcement learning (i.e., outside of the context of fear stimuli) remains poorly understood. Here, we investigate brain and behavioral differences in general reinforcement learning between adult women with and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 72 publications
1
32
0
Order By: Relevance
“…This evidence is mixed both in regard to both presence and absence of abnormalities, as well as the specific behavioral and circuit dynamics implicated as abnormal across studies. The most consistent finding across studies and paradigms is a hyporesponsivity of the ventral striatum to monetary and “social” reward receipt ( Elman et al, 2009 ; Felmingham et al, 2014 ; Ross et al, 2018 ; Sailer et al, 2008 ), which is consistent with the motivational deficits, diminished interest (as diminished subjective “liking” of a reward will induce less motivation or interest in obtaining that reward in the future), and diminished capacity to feel positive emotions that are frequently observed to characterize individuals with the PTSD diagnosis ( Hassija et al, 2012 ). Moreover, greater severity of PTSD diminished positive affect symptoms were observed to relate to more severe deficits in ventral striatal engagement to both monetary and social reward ( Elman et al, 2009 ; Felmingham et al, 2014 ), which further highlights the plausibility of this convergence.…”
Section: Reward Circuit Function and Behavior In Ptsdmentioning
confidence: 96%
See 1 more Smart Citation
“…This evidence is mixed both in regard to both presence and absence of abnormalities, as well as the specific behavioral and circuit dynamics implicated as abnormal across studies. The most consistent finding across studies and paradigms is a hyporesponsivity of the ventral striatum to monetary and “social” reward receipt ( Elman et al, 2009 ; Felmingham et al, 2014 ; Ross et al, 2018 ; Sailer et al, 2008 ), which is consistent with the motivational deficits, diminished interest (as diminished subjective “liking” of a reward will induce less motivation or interest in obtaining that reward in the future), and diminished capacity to feel positive emotions that are frequently observed to characterize individuals with the PTSD diagnosis ( Hassija et al, 2012 ). Moreover, greater severity of PTSD diminished positive affect symptoms were observed to relate to more severe deficits in ventral striatal engagement to both monetary and social reward ( Elman et al, 2009 ; Felmingham et al, 2014 ), which further highlights the plausibility of this convergence.…”
Section: Reward Circuit Function and Behavior In Ptsdmentioning
confidence: 96%
“…Utilizing a two-arm bandit task (i.e. participant has a choice between two options on each decision portion of the trial and is attempting to pick the option that provides the largest monetary payoff in the outcome phase) in women with PTSD due to assault, the investigators examined how computational estimates of stimulus value (the degree to which a particular choice stimulus during the decision phase was perceived to be associated with likelihood of a future reward) and prediction errors (the difference between the outcome expected and the outcome received) differed as a function of diagnostic status, as well as how the information components of value and prediction errors may be differentially reflected in brain circuitry ( Ross et al, 2018 ). The authors utilized the common Rescorla-Wagner computational model of reinforcement learning ( Sutton and Barto, 1998 ) to derive trial-by-trial estimates of stimulus value and prediction errors for each individual, and then examined how these component estimates related to time courses of BOLD activity (separated by independent component analysis-defined spatial networks) throughout the course of the task.…”
Section: Reward Circuit Function and Behavior In Ptsdmentioning
confidence: 99%
“…Previous approaches to computational modeling of PTSD have focused on defining changes in associative learning after traumatic experience (11-15). PTSD is thus framed as a consequence of underlying mechanisms for predicting threat based on previous associations .…”
Section: Resultsmentioning
confidence: 99%
“…Identifying PTSD with threat momentum may facilitate future neurobiological and translational studies of PTSD. Extensive work has shown that patients with PTSD have different learning rate parameters during fear and extinction learning (11-15) than controls in the formation of associations. This study extends these findings by offering a model of how the sequence of threat prediction errors may generate other associative learning alterations in PTSD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation